Implementasi Sistem Informasi Pengadaan di Sekolah (SIPLAH) Terhadap Efektivitas Pengelolaan Dana BOS di SLB Negeri 1 Tabanan - Gede Bagus Aditya Pramana Wibawa (Jurnal Widya Mahavira, 2026)
This study aims to determine the effectiveness of the implementation of the School Procurement Information System (SIPLah) on the management of School Operational Assistance (BOS) funds at SLB Negeri 1 Tabanan. This study used a qualitative descriptive approach with a phenomenological approach. Data collection techniques included observation and interviews with informants including the Principal, Vice Principal for Facilities and Infrastructure, and Financial Administrator. The results indicate that the implementation of SIPLah complies with Government Regulation No. 48 of 2008 concerning Education Funding. Procurement of goods and services through SIPLah is carried out in four stages: searching, ordering, receiving, and payment. SIPLah provides significant benefits to schools by simplifying the procurement of goods and services and increasing transparency, efficiency, and accountability in the management of BOS funds. Monitoring the use of BOS funds is facilitated by the system's purchase history and automatic documentation features.